Identification of biomarker genes from multiple studies for abiotic stress in maize through machine learning - Nazari, Leyla; Zinati, Zahra; Bagnaresi, Paolo (Journal of biosciences, 2024)
Abiotic stresses are major limiting factors for maize growth. Therefore, exploration of the mechanisms underlying the response to abiotic stress in maize is of great interest. Toward this end, we performed integration of the feature selection method into the meta-analysis of microarray gene expression. Following extraction of raw data, normalization, and batch effect removal, the data were merged into one expression profile. Differentially expressed genes (DEGs) between control and abiotic conditions were used for the feature selection algorithm to find the minimum features for high-performance classification. Feature selection was performed using a correlation-based feature selection (CFS) algorithm, considering features with a coefficient of 0.7 to 1. Different algorithms of Bayes, Functions, Lazy, Meta, Rules, and Trees were then tested in order to classify the samples and find the best performance classifier in each group. Moreover, the biological pathways and promoter motif analysis of selected genes were identified. The superior and overall performance of classification using all features (DEGs) were 98.86% (Multilayer Perceptron) and 81.25%, respectively. Classification based on feature selection resulted in an average accuracy of 94.69% and 93.56% with 33 and 12 features, respectively. Subsequently, gene ontology and promoter analysis were performed for the 12 selected biomarker genes. Five of them were downregulated and 7 were upregulated. ABRE, unnamed-1, G-box, and G-Box are motifs related to genes involved in several abiotic stress responses and are located upstream of at least nine probes in our study. This study revealed key genes associated with tolerance to abiotic stress in maize. Graphical abstract